Financial Liberalisation and Gross Domestic Savings in Southern African Development Community (SADC) Countries - Gonese, Dorcas; Sibanda, Kin; Garidzirai, Rufaro; Akande, Joseph Olorunfemi (Universitas Syiah Kuala, 2025)
Objective This study examines the impact of financial liberalisation on domestic savings in the Southern African Development Community (SADC) countries. Despite reports suggesting unfavourable outcomes in many countries, it addresses the lack of documented evidence regarding the impact of financial liberalisation on savings.Design/Methodology The study analyses data from 16 SADC countries from 1980 to 2019, utilising the panel Autoregressive Distributed Lag (ARDL) approach. The hypothesis tested is that financial liberalisation, as one of the structural reforms, has contributed significantly to the growth of savings rates.Results The findings show that financial liberalisation measures, particularly those related to interest rates and financial depth, substantially positively impact domestic savings in SADC.Research limitations/implications The study only focused on SADC countries. The study concludes that financial liberalisation is crucial for promoting domestic savings. The governments and policymakers in SADC countries are advised to consider implementing interest rate changes and enhancing financial efficiency monitoring to foster long-term improvements in domestic savings.Novelty/Originality The paper provides an original perspective as it incorporates the financial development and the degree to which external financing affects savings in the SADC region. Again, leveraging the most recent data can capture current trends and the effects of recent financial policies on SADC domestic savings. The study employs cutting-edge econometric methods, such as the panel ARDL estimation methods, which enable both short- and long-term analysis and offer new insights that traditional models might overlook.